2020
DOI: 10.1007/s10614-020-10042-0
|View full text |Cite
|
Sign up to set email alerts
|

Explainable Machine Learning in Credit Risk Management

Abstract: The paper proposes an explainable Artificial Intelligence model that can be used in credit risk management and, in particular, in measuring the risks that arise when credit is borrowed employing peer to peer lending platforms. The model applies correlation networks to Shapley values so that Artificial Intelligence predictions are grouped according to the similarity in the underlying explanations. The empirical analysis of 15,000 small and medium companies asking for credit reveals that both risky and not risky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
110
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(115 citation statements)
references
References 13 publications
1
110
0
4
Order By: Relevance
“…When a financial institution trains a credit risk model, prediction accuracy is of paramount importance, i.e., companies aim to maximize revenue through model accuracy. Yet, interpretability is a legal requirement [ 22 ]. This constitutes a conundrum for most companies [ 21 ]: it is generally accepted that there exists a complex trade-off between accuracy and interpretability, whereby maximization of one comes at the expense of the other.…”
Section: Related Workmentioning
confidence: 99%
“…When a financial institution trains a credit risk model, prediction accuracy is of paramount importance, i.e., companies aim to maximize revenue through model accuracy. Yet, interpretability is a legal requirement [ 22 ]. This constitutes a conundrum for most companies [ 21 ]: it is generally accepted that there exists a complex trade-off between accuracy and interpretability, whereby maximization of one comes at the expense of the other.…”
Section: Related Workmentioning
confidence: 99%
“…In order to overcome these limitations, new explainable methods have been introduced in the last 5 years. Explainable Artificial Intelligence (XAI) is a relatively new field of Artificial Intelligence and it comprises a large amount of techniques that combines ML algorithms with explanatory techniques to develop explainable solutions that have been extensively applied in different domains (Gunning, 2017;Adadi and Berrada, 2018;Biecek, 2018;Guidotti et al, 2018;Miller, 2019;Arrieta et al, 2020;Bussmann et al, 2020). Recent work has suggested that XAI methods constitute a fundamental pillar for personalized medicine, including individualized interventions and targeted treatments (Vu et al, 2018;Fellous et al, 2019;Langlotz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Misheva et al [1] underline that AI offers great opportunities for enhancing the customer experience, democratizing financial services, ensure consumer protection and significantly improve risk management. In this field, Bussmann et al [2] argue that Artificial Intelligence models can be used in credit risk management and, in particular, in measuring the risks that arise when credit is borrowed employing peer to peer lending platforms. Islam et al [3] recall that a fundamental challenge for A.I.-based prediction models is the extent to which the internal working mechanisms of an AI system can be explained in human terms.…”
Section: Introductionmentioning
confidence: 99%